The Perception of Global Citizenship Education Among School Teachers in India: A Survey - Nikalje, Varada M. (THE PRIMARY TEACHER, 2022)
The National Education Policy (NEP) 2020 envisages many changes in education. It also includes new and contemporary issues important for school education. One of them is Global Citizenship Education (GCED). GCED is based on the principle of respect and appreciation of various cultures, different forms of expression, and diverse human realities to ensure an equitable educational environment. The successful implementation of GCED requires a theory-based understanding of the concept by teachers and teacher-educators, and other informal and non-formal settings. A globalised world and its challenges are what future generations are likely to inherit. Hence, it is essential that today’s education helps to prepare children for tomorrow’s world. This paper sheds light on the teachers’ understanding of the concept and practicality of implementing the GCED values in school curricula.